72 Eight injections of Collagenase Clostridium Histolyticum May Be Effective in Calcified Plaques. Issue 1 (1st April 2022) - Masterson, T; Ranier, Q; Hauser, N; Kava, B; Ramasamy, R
ABSTRACT: Introduction: Peyronie's disease (PD) is the result of abnormal tissue healing in the tunica albuginea resulting in an inelastic plaque. In some instances, plaques will calcify. Several studies question the efficacy of Collagenase Clostridium Histolyticum (CCH) in calcified plaques leading to a belief that calcification is associated with failure of medical treatment and an increased risk of surgical intervention. Our objective is to measure changes in curvature before and after treatment of calcified plaques with CCH. Objective: To determine change in curvature of calcified plaques treated with 8 injections of CCH Methods: We prospectively evaluated PD plaques using ultrasound in all men presenting with PD starting November, 2018. Plaques were evaluated in the flaccid state and curvature was measured after the injection of intracavernosal Trimix using goniometer. We utilized a standardized system of plaque typing: type 1: thickening of the tunica albuginea without acoustic shadowing, type 2: a moderately calcified plaque with a typical ultrasound shadow, type 3: a severely calcified plaque complete acoustic shadowing. We measured pre and post CCH curvature 6 months after all eight injections using he standard manufacturer protocol. All patients were instructed on home modeling. Paired T-t was used to compare pre and post measurements. Results presented as means± standard deviations. Results: We identified 19 men with calcified PD who completed all 8 injections of CCH. Mean age and curvature were 61±7 years and 55±22 degrees. Of the 19 men, 7 had type 3 plaques and 12 had type 2 plaques. There were no differences in patient age however there was a difference in baseline curvature between type 2 and 3 plaques (55±17 vs 75±17 degrees p<0.05). Curvature improved by an average of 25±20 degrees p<0.05. Interestingly, as a group, type 3 plaques improved by 37±23 degrees compared to 18±15 degrees for Type 2, however this difference was not significant Conclusions: In our small cohort, 8 injections of CCH appear to be an effective therapy for men with calcified PD plaques. Interestingly, CCH remained effective even in severely calcified PD. A larger study including a comparison of non-calcified PD is needed. Disclosure: Yes, this is sponsored by industry/sponsor: ISR from Endo Pharmaceuticals Clarification: Industry funding only - investigator initiated and executed study Any of the authors act as a consultant, employee or shareholder of an industry for: Endo Pharmaceuticals